A systematic review of intervention studies for young children with emotional and behavioral disorders: identifying the research base. Issue 2 (6th March 2021) - McKenna, John William; Brigham, Frederick; Garwood, Justin; Zurawski, Lindsay; Koc, Murat; Lavin, Carlos; Werunga, Robai
Abstract: Schools continue to experience difficulty meeting the needs of young children who are formally identified as having an emotional and/or behavioural disorder (EBD). Although schools are mandated to use evidence‐based practices to improve student outcomes, such practices must first be identified before they can be employed. Systematic reviews of intervention studies are commonly performed to identify evidence‐based practices, make recommendations for service delivery, and identify areas for future research that are needed to inform practice. At this time, researchers have yet to perform a systematic review of intervention studies involving young children identified with EBD – early childhood (EC) – grade 2. The purpose of this study was to identify and describe published school‐based intervention research for this student population. Studies meeting selection criteria were evaluated according to the relevant What Works Clearinghouse (WWC) Design standards to identify studies with strong internal validity that reported positive effects. Twenty‐nine manuscripts reporting 30 intervention studies were identified. Findings suggest that practitioners must primarily rely on their professional judgement and values guided by principles embedded in their training when planning instruction and support for young children with EBD due to the absence of high‐quality intervention research. Additional rigorous evaluations are needed so that practice is better informed by science. Recommendations for practice, areas for future research, and study limitations are discussed.